1992
DOI: 10.1111/j.1398-9995.1992.tb00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Twelve months, treatment with inhaled salmeterol in asthmatic patients

Abstract: Salmeterol is a new beta 2-receptor agonist with a prolonged duration of action after inhalation, exceeding 12 h in most patients. We have performed a 12-month open follow-up study on 11 patients with reversible asthma. All patients were given salmeterol inhalations (50 micrograms twice daily). Additional asthma treatment included inhaled corticosteroids in all patients, and oral slow-release theophylline or beta 2-receptor agonists in a minority of patients (3 and 1, respectively). Before salmeterol treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…These results are in keeping with those obtained from two previous studies [8,9], both of which also showed no change in salbutamol response after chronic treatment with salmeterol. However, both of these were open studies with no control group.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are in keeping with those obtained from two previous studies [8,9], both of which also showed no change in salbutamol response after chronic treatment with salmeterol. However, both of these were open studies with no control group.…”
Section: Discussionsupporting
confidence: 82%
“…However, both of these were open studies with no control group. In one of the studies [8], salmeterol treatment lasted just 2 weeks, whilst in the other [9], the duration of treatment was 12 months. In both of these studies, patients continued using short acting β 2 -agonists as rescue medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5a). After the completion of this investigation, we followed the patients in an open study in the same way for 12 months [24]. The dose-effect curve for inhaled salbutamol after 3, 6, 9, and 12 months' treatment showed a well-maintained maximal response without any sign of development of tolerance (Fig.…”
Section: Development Of Tachyphylaxismentioning
confidence: 99%
“…No inhibitory effect on the maximal bronchodilator effect was observed after the salmeterol treatment period. Data are shown as FEV\ (% of maximum value for each patient; from[44]); (b) The bronchodilator effect of inhaled salbutamol (100, 300, and 900 J.Lg) before and after 6 and 12 months' treatment with salmeterol (50 J.Lg twice daily), 24 h after the last dose of salmeterol (from[24]). …”
mentioning
confidence: 99%